2021
DOI: 10.3389/fpsyg.2021.692404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wearing Surgical Mask on Interpersonal Space Perception Between Mainland Chinese and Taiwanese People

Abstract: Wearing face masks and maintaining social distancing of 1.5m are two common preventive measures against the spread of COVID-19. However, the interaction of these preventive measures in interpersonal space (IPS) perception remains unknown. This study evaluated the effects of wearing surgical masks, sex dyads, and approaching patterns on IPS judgment. Data were collected from participants from Mainland China (n=100) and Taiwan (n=100) through an online survey. Therefore, the regional differences were also examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
5
23
0
Order By: Relevance
“…These ndings align with the notion of the behavioral immune system (BIS), a unique motivational mechanism with a set of emotional, cognitive, and behavioral adaptations designed to prevent infectious diseases by rapidly identifying potential pathogenic sources in the environment and encouraging their avoidance (Schaller & Park, 2011). Accordingly, allowing a larger IPD from prospective sick people would inhibit contact with pathogens in the rst place, thus preventing infection transmission and bene tting one's welfare (Lee & Chen, 2021;Lisi et al, 2021;Sorokowska et al, 2017).…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…These ndings align with the notion of the behavioral immune system (BIS), a unique motivational mechanism with a set of emotional, cognitive, and behavioral adaptations designed to prevent infectious diseases by rapidly identifying potential pathogenic sources in the environment and encouraging their avoidance (Schaller & Park, 2011). Accordingly, allowing a larger IPD from prospective sick people would inhibit contact with pathogens in the rst place, thus preventing infection transmission and bene tting one's welfare (Lee & Chen, 2021;Lisi et al, 2021;Sorokowska et al, 2017).…”
Section: Introductionsupporting
confidence: 65%
“…While the link between IPD and pathogen avoidance has been previously put together, most research on this topic focuses on individuals with disabilities (for a review, see Park et al, 2003), on labeling confederates with the diagnosis of a contagious disease (e.g., Lisi et al, 2021;Mooney et al, 1992;Toppenberg et al, 2015), or, most recently, on wearing protective equipment (e.g., Iachini et al, 2021;Lee & Chen, 2021). However, faces are ideal when searching for tness-relevant information, and, as such, understanding how people behave toward facial deviations is of the utmost importance, especially when considering social processes such as prejudice and discrimination (Schaller & Park, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes in relation to the impact of face covering use on physical distancing were mixed and varied depending on the type of study. Findings from the majority of lab experiments (10 of 13) indicated that physical distancing was lower in conditions where a face covering was used by another person compared with conditions where it was not [20][21][22][23][24][25][26][27], [28: two different studies], and two of these studies also found that physical distancing was lower when a face covering was used by the self [28: two different studies]. Additionally, one of these studies investigated how physical distancing in conditions with and without face covering use compared with a baseline measure (that is, physical distancing outside the context of face covering use) [20].…”
Section: Physical Distancing (See Table 2a In S4 Appendix For Full De...mentioning
confidence: 99%
“…After all, research on this topic showed that people preferred to keep farther apart from other individuals during the pandemic (40,41), in line with social distancing guidelines for the avoidance of virus transmission. It was also shown that preferred IPD is sensitive to the wearing of face masks (18,(42)(43)(44) and to others' infection status (45). Moreover, changes in distance preferences have been found to be associated with individual differences in anxiety (42,46) and in perceived risk of infection (40,46).…”
Section: Introductionmentioning
confidence: 99%